The development of a new parameter for tracking post-transcriptional regulation allows the detailed map of the Pseudomonas aeruginosa Crc regulon. Issue 1 (December 2018) - Corona, Fernando; Reales-Calderón, Jose; Gil, Concha; Martínez, José
Abstract Bacterial physiology is regulated at different levels, from mRNA synthesis to translational regulation and protein modification. Herein, we propose a parameter, dubbed post-transcriptional variation (PTV), that allows extracting information on post-transcriptional regulation from the combined analysis of transcriptomic and proteomic data. We have applied this parameter for getting a deeper insight in the regulon of thePseudomonas aeruginosa post-transcriptional regulator Crc.P. aeruginosa is a free-living microorganism, and part of its ecological success relies on its capability of using a large number of carbon sources. The hierarchical assimilation of these sources when present in combination is regulated by Crc that, together with Hfq (the RNA-binding chaperon in the complex), impedes their translation when catabolite repression is triggered. Most studies on Crc regulation are based either in transcriptomics or in proteomics data, which cannot provide information on post-transcriptional regulation when analysed independently. Using the PTV parameter, we present a comprehensive map of the Crc post-transcriptional regulon. In addition of controlling the use of primary and secondary carbon sources, Crc regulates as well cell respiration, c-di-GMP mediated signalling, and iron utilization. Thus, besides controlling the hyerarchical assimilation of carbon sources, Crc is an important element for keeping bacterial homeostasis and, consequently, metabolic robustness.